OCORRÊNCIA DE ANTIDEPRESSIVOS RESIDUAIS E CAFEÍNA EM SEDIMENTOS E LODOS DE ESGOTO: DESENVOLVIMENTO DE METODOLOGIA ANALÍTICA E ESTUDOS DE FOTODEGRADAÇÃO E SORÇÃO - COSTA JUNIOR, ISMAEL LAURINDO (2017)
The identification of emerging pollutants in environmental matrices has become increasingly frequent. Among these pollutants, the presence of drugs has great relevance, since this category of contaminants includes a large number of active substances widely consumed worldwide. Neuroactive drugs, such as antidepressants, have shown a significant increase in prescription and consumption in the last decades. These drugs present direct action on the nervous system and are considered as of great environmental concern, since studies have verified their presence in effluent treatment plants, in superficial waters, sediments and in tissues of aquatic organisms. The wide variety of microcontaminants substances makes individual monitoring actions difficult, with the use of anthropic pollution markers being introduced as direct indicators for some classes of pollutants such as drugs. The use of caffeine as a chemical marker for residual medicines is justified by its physicochemical properties and the similarity of the routes of introduction and transport in the compartments. Initially, it was proposed the optimization of a method for the simultaneous extraction of frequent-use antidepressants (citalopram, venlafaxine, fluoxetine, sertraline and amitriptyline) and caffeine based on the use of solvents aided by microwave and HPLC-PDA. In the optimization, the simplex-centroid experimental designs for extractive phase composition were applied, and a central rotational compound (CCRD) 2³ was used to adjust the extraction protocol for the working pH, lower solvent use and processing time. The analysis of variance (ANOVA) and the study of the lack of fit were used to evaluate the significance of the adjustments at the 95% confidence level. The desirability function was the optimization tool used to obtain the ideal conditions and presented values close to 1.0, which indicated a significant response for both designs. The composition obtained for the liquid phase in the simultaneous extraction in the two matrices was a binary mixture of methanol and acetonitrile in the proportion of 45:55 and 53:47 (v / v) for sludge and sediment respectively. The optimized conditions were pH 3, volume of 4 mL of the solvent extractor and 3 cycles of extractions for the sewage sludge. For the sediment the values were pH 11, volume of 3 mL of the solvent mixture and 4 cycles of extractions. A fast method for the simultaneous determination of analytes based on optimized microwave-assisted solvent extraction with HPLC-PDA detection was proposed. The analytical method was validated and considered satisfactory for quantifications in sewage sludge and sediments. The method was applied to samples of sewage sludge and sediments from the Itaipu reservoir region. The results confirm the presence of the analytes in the sewage sludge and indicate the treatment plant residues as a route of insertion of micropollutants into the local environment, since the antidepressants were also found in the river sediments. In the next step, the degradation of the analytes was studied by direct photolysis. Degradation tests were performed using a 100 mL capacity bench reactor equipped with an artificial radiation source composed of a high pressure mercury vapor lamp (254 nm) and natural insolation. The degradation products were evaluated qualitatively in the tests using water and artificial radiation source. The experimental data were adjusted to kinetic models in order to obtain the reaction rates and the half-life in the studied conditions. Further degradation was observed in complex matrices such as sewage and surface waters, indicating that the persistence also depends on dissolved species capable of being part of the degradation mechanisms. The kinetics that apparently describes the phototransformation of the compounds under the studied conditions was that of pseudo-first order. The qualitative study of the by-products formed in the artificial process in aqueous solution made it possible to confirm the transformation of the analytes. The results obtained using sunlight suggests the persistence of microcontaminants investigated when exposed to this source of radiation in the environment. Finally, considering the interaction of the investigated microcontaminants with the solid compartment as an important factor when considering their fate in the ecosystems, sorption and desorption were studied in freshwater sediments and sewage treatment plant sludges. The experiments were conducted by the batch method and the determinations were performed by ultraviolet spectrophotometry and by HPLC-PDA. The experimental data were fitted to kinetic models of pseudo-first and pseudo-second order. Sorption and desorption were studied by adjusting the linear and Freundlich isotherms. The partition was evaluated by the coefficients kd, koc and by the calculation of the desorption percentage. The kinetic study indicated pseudo-first-order behavior. The interpretation of sorption by the Freundlich isotherm proved to be satisfactory for all analytes and matrices. The evaluation of the model constants and the kd and koc coefficients was consistent with other studies and indicated agreement between the hydrophobicity of the drugs and their affinity for the solid matrices. The high percentages obtained for the desorption suggest mobility of the analytes, being this one more intense in the sludge than in the sediment, since there are particularities of composition in each matrix and, therefore, mechanisms differentiated in terms of energy and affinity with the studied substances. The panorama obtained in this research allows us to consider that the residual antidepressants and caffeine presented persistent behavior to natural processes such as photolysis and present tendencies to the solid compartment accumulation, with potential mobility, depending on environmental conditions, such as pH and matrix composition. Due to these characteristics can be detected in sewage sludge and sediment treatment sludge, and present possibility of exposure to biota in aquatic ecosystems.